Dampak Penutupan TPA Tlekung Kota Batu terhadap Pengelolaan Sampah bagi Masyarakat di Lingkungan Sekitar Desa Tlekung Kota Batu - Salsabila, Helga; Hidayah, Nafisatul; Nisa, Aprilia Khoirun; Ningrum, Dian Eka Aprilia Fitria (Experiment: Journal of Science Education, 2023)
Waste from all areas of Batu City is dumped into one landfill located in Tlekung Village, Junrejo District. But for now, the landfill is still closed and it is not yet known when it will reopen. Waste management into compost is still running, but the delivery of waste from all over Batu City is stopped to centralize disposal at the landfill. On August 30, 2023, the landfill was officially closed. Some residents of Batu City requested that the landfill be closed for certain reasons. This research uses a qualitative approach with a case study design. Observation, interviews, and documentation were employed as data collection techniques. The gathered data underwent analysis through an interactive model encompassing data collection, reduction, display, and conclusion drawing. Triangulation involving techniques, sources, methods, and extended observation was implemented to ensure data validity. The closure of the Tlekung landfill has an impact on the waste management system, especially in Batu City, which was previously one in Tlekung landfill in Batu City to be managed by each village. In addition, the closure of the Tlekung landfill also has a positive impact and a negative impact. The positive impact is that the overall environmental quality will improve. The negative problem arising from this closure is residue, especially in the market area where it is not yet known where the waste should be disposed of.